2018
DOI: 10.3390/healthcare6020052
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Oral Health Status between International and Japanese University Student Patients in Japan

Abstract: Background: The number of international students enrolled in universities in Japan is increasing. To provide better oral care services for international students, we have to understand their oral environment and dental health behaviors. However, few studies have investigated the oral health status of international university students. The object of the present study was to clarify the current oral status of international university students. Methods: The subjects were students who visited the dental department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
2
8
1
Order By: Relevance
“…The present study reported that 69.5% of study participants have not visited a dental clinic during their stay in Korea, and this indicates low utilization of dental services among foreign students in Korea, with was found to be similar to the existing studies [7][8][9] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study reported that 69.5% of study participants have not visited a dental clinic during their stay in Korea, and this indicates low utilization of dental services among foreign students in Korea, with was found to be similar to the existing studies [7][8][9] .…”
Section: Discussionsupporting
confidence: 89%
“…A comparative study of international and Japanese college students conducted in Japan showed that foreigners' oral health conditions were worse than those of Japanese and it was linked with the lower use of dental service 7) . In research by Shim et al 8) 65.3% of Chinese students residing in Korea had not visited the dentist during their stay in Korea, and Language barriers, economic burdens, and lack of information were found to be associated with low utilization of dental services.…”
Section: Introductionmentioning
confidence: 99%
“…The repair action could be supposed as a synergic activity of this pathway with different growth factors, such as epidermal growth factor (EGF), platelet-derived growth factor (PDGF), and fibroblast growth factor (FGF) [ 32 ]. In the present investigation, the baseline values showed no statistically significant differences in FMPS and FMBS in the Test and Placebo study groups, both of which exceeded 20%, which, in the literature, is associated with a high risk of progression of periodontal disease [ 20 , 22 , 33 , 34 ]. The rationale of the full mouth plaque and bleeding score is determined by the assessment of the mesial, distal, buccal, and palatal/lingual parts of the teeth by a dichotomous measurement (if present or absent) [ 35 , 36 , 37 ].…”
Section: Discussioncontrasting
confidence: 44%
“…These factor in play a crucial role in getting an adequate dental care and are known to negative affect OHRQ oL. 44,45 The relationship of education and income with OHRQoL was explored in the present study. Education was found to be a significant factor in relation to OHRQoL as higher education level was significantly related to the higher OHIP-EDENT score.…”
Section: Methods Of Cleaning N (%)mentioning
confidence: 99%